ANALISIS RISIKO USAHA PADA TOKO BAHAN KUE ARIEF 2 SUMENEP: PENDEKATAN MATRIKS RISIKO UNTUK PRIORITAS MITIGASI PADA UMKM - Diah Ajeng Kusuma Wardani Hamzah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Micro, small, and medium enterprises (MSMEs) face operational, economic, market, and marketing risks that may disrupt business continuity when they are not managed systematically. This study aims to identify, assess, evaluate, and formulate risk mitigation strategies for Arief 2 Baking Ingredients Store in Sumenep, Indonesia. A descriptive case-study approach was applied. Primary evidence was derived from direct observation of procurement, storage, distribution, and sales activities. Risks were assessed using a 5×5 risk matrix based on likelihood and impact, with the risk score calculated as R = L × I. Seven risks were identified: raw-material price changes, product damage due to storage conditions, overstock, understock, changes in consumer trends, business competition, and dependence on nearby customers. The highest scores were obtained by raw-material price changes and understock (16; high). Product damage, business competition, and customer dependence scored 12 (high), while overstock and changes in consumer trends scored 9 (medium). Priority mitigation measures include supplier diversification, safety stock and routine inventory monitoring, improved storage conditions and FIFO practices, procurement based on sales data, service improvement, and expansion through social media and delivery services. The findings indicate that a simple risk matrix can serve as a practical decision-support tool for MSMEs to prioritize risk controls.